Upaya Meningkatkan Sikap Ilmiah Mahasiswa Pendidikan Biologi STKIP YPM Bangko pada Mata Kuliah Biokimia Melalui Penerapan Pembelajaran Berbasis Praktikum - Rivo Yulse Viza (Eduscience Development Journal, 2019)
This study is aimed to analyze the improvement of scientific students’ attitude Biology Education in STKIP YPM Bangko in lecturing of Biochemistry. The design of this research is classroom action research with implementing practical based learning. Practical based learning is a method that could help students to find out the fact of theory that they had learned during it. This research had been organized on March until May 2016 at STKIP YPM Bangko. The parameter in this study is a scientific attitude with indicator; curiously, flexible attitude, critical atittude, honest, and accuracy. The result showed that Practical based learning has been performing well. Scientific attitude of student has increased by an average from 59,38% in the first cycle to 72,50% in the second cycle. It can be conclude that practical based learning an effective methode to improve scientific students’attitude Biology Education in STKIP YPM Bangko.